Corneal Total and Epithelial Thickness Measured by Sonogage Ultrasound Pachometry and High-resolution Optical Coherence Tomography. Issue 5 (May 2020) - Swarbrick, Helen A.; Kang, Pauline; Peguda, Rajini
Abstract : SIGNIFICANCE: This research questions the validity of using the Sonogage ultrasound (US) pachometer to measure corneal epithelial thickness and coincidentally provides confirmation for the conventional view of the mechanism of orthokeratology (OK) based on central epithelial thinning. PURPOSE: The Sonogage (Corneo-Gage Plus 1) pachometer uses A-scan US to measure total corneal thickness. It is claimed that this instrument can also measure corneal epithelial thickness. We sought to validate this claim by comparing total and epithelial thickness measurements with the Sonogage with those obtained with high-resolution optical coherence tomography (OCT). METHODS: Fourteen non–contact lens wearers and 14 subjects who had worn Paragon CRT OK lenses overnight for greater than 1 month were recruited. Three OCT and five US measurements were taken in one eye of each subject. Depending on normality of data, paired t tests or Wilcoxon tests were used to compare total and epithelial thicknesses measured with the Sonogage pachometer and the Tomey Casia OCT. Pearson or Spearman correlation analyses were used to examine relationships between measurements obtained with the two instruments. RESULTS: There was a significant difference in total corneal thickness measurements between the two instruments. Although a significant correlation was found ( r = 0.916, P < .001), the Sonogage consistently measured greater total corneal thickness than did the OCT (+19.5 ± 9.2 μm; P < .001). Epithelial thickness using the Sonogage showed little variation (range, 46.4 to 50.0 μm), whereas epithelial thickness using the OCT ranged from 30.7 to 54.7 μm. There was no significant correlation between epithelial thicknesses obtained with the two instruments ( r = −0.135, P = .49). Epithelial thickness measured by OCT was significantly thinner in OK wearers (35.8 ± 2.8 μm) than in nonlens wearers (46.7 ± 4.5 μm, P < .001). CONCLUSIONS: The Sonogage is not able to measure epithelial thickness in vivo, returning essentially identical measurements over a range of epithelial thicknesses. Optical coherence tomography measurements confirm the conventional view of the mechanism of OK based on central epithelial thinning.